Age-cohort analysis of arrest rates - Greenberg, David F. (Journal of quantitative criminology, 1985)
Logistic regressions of age-period-cohort models for city arrest rates are estimated with data from seven U.S. cities for the years 1970–1980 to study the dependence of officially designated criminality in select offense categories on age. A sensitivity analysis is carried out to determine how dependent the findings are on details of model specification.